CONTESTATION BETWEEN STATE LAW AND ISLAMIC LAW IN LEGAL PRACTICES AMONG INDONESIAN MUSLIMS (State Islamic University (UIN) of Sunan Ampel Surabaya, 2012)
BOOK REVIEW:Book title:Modernization, Tradition and Identity; The Kompilasi Hukum Islam and Legal Practice in the Indonesian Religious Courts Author:Euis NurlaelawatiNo. of Pages:297Year:2010Publisher:ICAS/ Amsterdam University Press